Harnessing climate services to support community resilience planning: lessons learned from a community-engaged approach to assessing NOAA’s National Water Model - Raub, Kristin B.; Laufer, Joshua; Flynn, Stephen E.; Daniels, Shemilore; Sivalingam, Trissha (Frontiers in Climate, 2024)
Inland and coastal flooding and other water-based natural disasters are projected to increase in severity, frequency, and intensity as global temperatures rise, placing a growing number of U.S. communities at risk. Governments at the local, state, and federal levels have been embracing resilience planning to better predict, mitigate, and adapt to such shocks and hazards. A growing number of climate services have been developed to aid communities engaged in these efforts to access, interpret, and make decisions with climate-related data and information.